Ultrathin rolled copper foil and preparation method thereof
By controlling the Fe, P and O content, and using baking and heating, oxygenation treatment and hot rolling processes, the problems of high pinhole ratio and poor plate shape of ultra-thin copper foil are solved, achieving low pinhole ratio and excellent The preparation of plate-shaped ultra-thin rolled copper foil improves the electrical conductivity and mechanical properties of the product.
Patent Information
- Application Number
- CN202411269609.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-20
AI Technical Summary
In the prior art, the pinhole ratio of ultra-thin copper foil has high plate shape and is not easy to control, resulting in current leakage, oxidative corrosion and decreased adhesion, affecting signal transmission efficiency and product quality.
By controlling the element content of Fe, P and O, the coordinated process of baking heating, oxygenation, vertical full-continuous casting, hot rolling, annealing and cold rolling can reduce the impact of impurities and temperature instability, ensuring the low level of copper foil Pinhole ratio and excellent plate shape.
It realizes the low pinhole ratio and excellent plate shape of ultra-thin rolled copper foil, improves the conductivity and mechanical properties, and ensures the reliability and market competitiveness of the product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper foil preparation, and in particular to an ultra-thin rolled copper foil and a preparation method thereof. Background Art
[0002] Rolled copper foil has good ductility, folding resistance, low surface profile, high density and conductivity. It is an important material for manufacturing shielding materials, flexible printed circuit boards (FPCs), and transparent conductive films (graphene). With the development of 5G / 6G communications, liquid crystal modules, new energy vehicles, and wearables. With the continuous advancement of production technology and the increasing requirements for product quality, users have increasingly stringent requirements on the thickness, surface quality, and plate shape of rolled copper foil. However, as the thickness of the rolled copper foil becomes thinner, the problems of high pinhole rate and poor plate shape become more prominent, making it difficult to prepare qualified ultra-thin rolled copper foil products. Pinholes in copper foil can cause current to leak from the surface of the copper foil, increase resistance, and reduce signal transmission efficiency; at the same time, pinholes expose the surface of the copper foil to the air, making it susceptible to oxidative corrosion; further, pinholes can also cause the adhesion between the copper foil and the substrate to decrease, affecting its fixing performance. Poor plate shape can cause poor bonding between the copper foil and the substrate, leading to problems such as cracking and wrinkling. Summary of the invention
[0003] In view of this, the present invention proposes an ultra-thin rolled copper foil to solve the problems of high pinhole rate, difficult to control plate shape, poor plate shape and the like of the ultra-thin copper foil in the prior art.
[0004] The technical solution of the present invention is implemented as follows: The present invention provides an ultra-thin rolled copper foil, which is composed of the following components in terms of mass percentage: Fe: ≤0.0005%, P: ≤0.0003%, O: 0.01-0.024%, and the balance is copper.
[0005] A second object of the present invention is to provide a method for preparing an ultra-thin rolled copper foil, the method comprising the following steps:
[0006] S1, baking and heating high-purity electrolytic copper to obtain a molten casting material;
[0007] S2, putting the molten casting material obtained in step S1 into a smelting furnace for smelting, and after the smelting is completely static, performing an oxygenation treatment to make the oxygen content evenly distributed in the copper liquid, and covering it with flake graphite after transferring it from the converter to the holding furnace, and then obtaining a rolled copper foil ingot by vertical full continuous casting;
[0008] S3, subjecting the rolled copper foil ingot obtained in step S2 to heating treatment and hot rolling treatment in sequence to obtain a hot-rolled strip;
[0009] S4, subjecting the hot-rolled strip obtained in step S3 to milling treatment, rough rolling treatment and heating treatment in sequence to obtain a rough-rolled strip;
[0010] S5, subjecting the rough-rolled strip obtained in step S4 to intermediate rolling, primary annealing, finish rolling and secondary annealing in sequence to obtain a thick rolled copper foil;
[0011] S6, rolling the thick rolled copper foil obtained in step S5 into a finished product to obtain an ultra-thin rolled copper foil.
[0012] In some embodiments, in step S1, the copper content of the high-purity electrolytic copper is ≥99.99%, and the parameters of the baking and heating treatment are as follows: temperature is 150-220° C., and time is 10-15 min.
[0013] In some embodiments, in step S2, the oxygenation treatment is carried out by introducing compressed air, and the dew point of the introduced compressed air is -60 to -70°C, and the moisture content is 0.005 to 0.02 g / m 3 .
[0014] In some embodiments, in step S2, the temperature of the holding furnace is 1160-1200°C.
[0015] In some embodiments, in step S3, the heating treatment is performed in a step beam furnace, and the parameters of the heating treatment are as follows: the heating atmosphere is an oxidizing atmosphere, the temperature is 920-950° C., and the air-fuel ratio of the oxidizing atmosphere is 1.1-1.2.
[0016] In some embodiments, in step S3, the parameters of the hot rolling process are as follows: a total of 7 passes, and the deformation amount of the 5th pass is 35-38%.
[0017] In some embodiments, in step S4, the parameters of the rough rolling process are as follows: a total of 7 passes are performed, and the roughness of the roll in the rough rolling process is 0.5 μm.
[0018] In some embodiments, in step S4, the heating treatment is performed in a bell-type furnace, and the parameters of the heating treatment are as follows: temperature is 520-550° C., and time is 4-6 hours.
[0019] In some embodiments, in step S5, the intermediate rolling process is performed for a total of 5 passes.
[0020] In some embodiments, in step S5, an annealing treatment is performed in an air cushion furnace with the following parameters: temperature of 620-650° C. and time of 20-30 s.
[0021] In some embodiments, in step S5, the finishing rolling process is performed for a total of 5 passes, and the roughness of the rolling roller is 0.15 μm.
[0022] In some embodiments, in step S5, the secondary annealing treatment is performed in a bell furnace, and the parameters are as follows: temperature is 280-320° C., and time is 3-5 h.
[0023] In some embodiments, in step S6, the finished product is rolled for a total of 4 times, and the parameters are as follows: the roughness of the roller is 0.1 μm, the inlet tension is 300-400 KN, the rolling speed is 600-700 m / min, and the rolling force is 180-200 KN.
[0024] In some embodiments, the ultra-thin rolled copper foil has a thickness of 4-6 μm, a pinhole rate of 3-7 pinholes / 10,000 meters, and a plate shape of 1-3I.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] This technical solution reduces the influence of impurities on pinhole formation by selecting and processing raw materials; reduces the influence of excessively high or low temperatures on the quality of copper foil ingots by controlling the temperature during smelting and casting; reduces the probability of pinhole defects at each stage by coordinated control of heating atmosphere, hot making, annealing and cold rolling, improves the shape of the foil, and ensures that ultra-thin rolled copper foil can achieve the purpose of low pinhole rate and excellent shape under the premise of meeting the thickness requirements. Compared with existing methods, this method has the characteristics of excellent process technology, strong market competitiveness and significant economic benefits. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.
[0030] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.
[0031] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.
[0032] In the prior art, as the thickness of the rolled copper foil becomes thinner, the problems of high pinhole rate and poor plate shape become more prominent, and it is difficult to prepare qualified ultra-thin rolled copper foil products. In order to solve the above technical problems, the present invention provides an ultra-thin rolled copper foil. The ultra-thin rolled copper foil is composed of the following components in mass percentage: Fe: ≤0.0005%, P: ≤0.0003%, O: 0.01-0.024%, and the balance is copper; in the present invention, iron and phosphorus are impurity elements and need to be strictly controlled. Specifically, the presence of iron will form a solid solution, resulting in an increase in resistivity, thereby reducing the electrical conductivity of copper. Iron is a metal that is easily oxidized. When it exists in copper, especially in a humid or sulfur-containing environment, it will accelerate the corrosion process of copper. This local corrosion effect, the so-called "dissimilar metal contact corrosion", may produce spots or holes on the surface of the copper foil, reducing its service life and reliability. In addition, the hardness of iron is higher than that of copper. When iron exists in the form of impurities, it will form hard spots in the copper matrix, which may reduce the ductility and machinability of the copper foil. During the rolling and forming process, these hard spots may cause cracks and fractures, affecting the quality of the finished product. Therefore, it is necessary to strictly control the amount of iron in the copper foil. Phosphorus will cause alloying of copper, which may cause increased brittleness and reduce the ductility and welding performance of the copper foil. Phosphorus will also affect the conductivity of the copper foil. Excessive phosphorus content will reduce the conductivity of the copper foil. In addition, phosphorus may form a brittle layer on the surface of the copper foil, affecting its surface quality. In summary, the present invention can avoid the negative impact on the production of rolled copper foil by controlling the elemental composition of iron and phosphorus.
[0033] Although the present invention controls the content of iron and phosphorus, the present invention dopes oxygen. In the prior art, oxygen is generally controlled or removed as an impurity element. However, in the present invention, a certain composition of oxygen is used, and its purpose is that an appropriate amount of oxygen content can purify the matrix, improve the conductivity and eliminate the brittleness of the grain boundary. Trace oxygen can improve the thermal processing performance of the copper strip, making the copper strip easier to deform and less likely to break during the processing of rolling, bending and stretching. This is because oxygen can form fine oxide particles, which helps to control the grain size and inhibit grain growth, thereby improving the uniformity and processing performance of the material. At the same time, trace oxygen can combine with hydrogen in copper to form unstable water vapor or hydroxide, thereby reducing the solubility of hydrogen in copper and avoiding hydrogen embrittlement, which is beneficial to the long-term stability and reliability of the copper strip. An appropriate amount of oxygen plays a certain oxidation chemical role on the impurity elements between the grains, and purifies the matrix to a certain extent. Trace oxygen can oxidize trace impurities Fe and P in copper and improve the conductivity of copper. Cu2O formed after adding O can react with impurity elements such as Bi, Sb, As, etc., to form spherical particles with high melting points distributed in the grains, eliminating the brittleness of the grain boundaries and improving the processing performance of the copper foil. However, excessive oxygen can reduce the plasticity of copper. Excessive oxygen may cause brittle phases to appear in copper, affecting its ductility and toughness. Especially under high-temperature processing or use conditions, the aggregation of oxides may become a crack source, reducing the mechanical strength and life of the material. In summary, the present invention needs to strictly control the content of oxygen elements so that it can play its positive effects and avoid its negative effects.
[0034] A second object of the present invention is to provide a method for preparing an ultra-thin rolled copper foil, the method comprising the following steps:
[0035] S1, baking and heating high-purity electrolytic copper to obtain a molten casting material;
[0036] S2, putting the molten casting material obtained in step S1 into a smelting furnace for smelting, and after the smelting is completely static, performing an oxygenation treatment to make the oxygen content evenly distributed in the copper liquid, and covering it with flake graphite after transferring it from the converter to the holding furnace, and then obtaining a rolled copper foil ingot by vertical full continuous casting;
[0037] S3, subjecting the rolled copper foil ingot obtained in step S2 to heating treatment and hot rolling treatment in sequence to obtain a hot-rolled strip;
[0038] S4, subjecting the hot-rolled strip obtained in step S3 to milling treatment, rough rolling treatment and heating treatment in sequence to obtain a rough-rolled strip;
[0039] S5, subjecting the rough-rolled strip obtained in step S4 to intermediate rolling, primary annealing, finish rolling and secondary annealing in sequence to obtain a thick rolled copper foil;
[0040] S6, rolling the thick rolled copper foil obtained in step S5 into a finished product to obtain an ultra-thin rolled copper foil.
[0041] This technical solution reduces the influence of impurities on pinhole formation by selecting and processing raw materials; reduces the influence of excessively high or low temperatures on the quality of copper foil ingots by controlling the temperature during smelting and casting; reduces the probability of pinhole defects at each stage by coordinated control of heating atmosphere, hot making, annealing and cold rolling, improves the shape of the foil, and ensures that ultra-thin rolled copper foil can achieve the purpose of low pinhole rate and excellent shape under the premise of meeting the thickness requirements. Compared with existing methods, this method has the characteristics of excellent process technology, strong market competitiveness and significant economic benefits.
[0042] Further, in step S1, the copper content of the high-purity electrolytic copper is ≥99.99%, and the parameters of the baking and heating treatment are as follows: the temperature is 150-220°C, and the time is 10-15min. The present invention first bakes and heats the raw materials to remove water and oil on the surface to prevent impurity elements from mixing into the melt during the subsequent smelting and heat preservation process, thereby increasing the gas content of the melt and affecting the internal quality of the ingot.
[0043] Furthermore, in step S2, the oxygenation treatment is carried out by introducing compressed air, and the dew point of the introduced compressed air is -60 to -70°C, and the moisture content is 0.005 to 0.02 g / m 3 The present invention can not only achieve the purpose of increasing the oxygen content by introducing compressed air, but also promote the escape of dissolved gas (such as hydrogen) in the copper liquid by introducing compressed air into the copper liquid, avoid the formation of pores during cooling and solidification, thereby improving the density and mechanical properties of the copper alloy, and furthermore, by accurately controlling the amount of compressed air introduced, the oxygen content can be adjusted to within the target range, and furthermore, it can ensure that the oxygen content in the copper liquid is evenly distributed, avoid the aggregation of local oxides, and help improve the quality and performance consistency of the final product.
[0044] The purpose of further limiting the dew point value and moisture content of compressed air in the present invention is to avoid hydrogen generated by the decomposition of water in high-temperature copper liquid, and to prevent water vapor from reacting with copper liquid to form hydrated oxides, both of which may affect the quality of copper alloy. Therefore, in this technical solution, relevant key process parameters of compressed air are strictly controlled.
[0045] Further, in step S2, the temperature of the holding furnace is 1160-1200° C. The present invention transfers the copper liquid that has been subjected to oxygenation treatment to the holding furnace, and sets the temperature of the holding furnace to between 1160-1200° C., in order to ensure the fluidity of the copper liquid and prevent oxidation, and then covers it with flake graphite, which can reduce oxidation caused by contact between the copper liquid and the air, and the graphite layer can effectively isolate the air, reduce air intake and copper liquid oxidation slag, and also play a role in heat preservation; after reaching a stable state in the holding furnace, the copper liquid will be transported to a vertical full-continuous casting machine, and this casting method can continuously produce long strips of ingots, which is particularly suitable for producing copper foil ingots with uniform thickness.
[0046] Furthermore, in step S3, the heating treatment is carried out in a step furnace, and the parameters of the heating treatment are as follows: the heating atmosphere is an oxidizing atmosphere, the temperature is 920-950°C, and the air-fuel ratio of the oxidizing atmosphere is 1.1-1.2. In the present technical solution, an oxidizing atmosphere is used as the heating atmosphere, and a slightly larger amount of oxygen than required for complete combustion is supplied, which means that there will be an additional supply of oxygen during the heating process, which helps to form a thin oxide film on the surface of the copper billet, thereby preventing defects such as hydrogen embrittlement caused by the reaction of oxygen in the copper with reducing gases such as hydrogen due to the atmosphere not being an oxidizing atmosphere, thereby affecting the subsequent performance of the copper foil. Within the temperature range of 920-950°C, the entire copper ingot will be completely and evenly heated, which is convenient for subsequent hot rolling treatment, and can also promote the reorganization of the internal crystal structure, eliminating casting stress and structural inhomogeneity that may occur during the casting process.
[0047] Further, in step S3, the parameters of the hot rolling process are as follows: a total of 7 passes, and the deformation of the 5th pass is 35-38%. In the present technical solution, the hot rolling is performed for a total of 7 passes, and each pass will further reduce the thickness of the material and increase its length. The present invention sets the deformation of the 5th pass to 35-38%, which means that in this rolling, the thickness of the material will be reduced by 35-38%. The larger deformation of this pass helps to make the rolling force of the entire strip during hot rolling compressive stress rather than tensile stress, thereby effectively welding relatively small defects, improving the internal quality of the strip, and thus improving the organization and mechanical properties of the material.
[0048] Further, in step S4, the parameters of the rough rolling process are as follows: a total of 7 passes, and the roughness of the rollers in the rough rolling process is 0.5 μm. In the present invention, the rough rolling process is divided into 7 passes, each of which will further reduce the thickness of the copper strip, while improving its surface flatness and mechanical properties. On this basis, combined with the 0.5 μm roller roughness, the surface of the copper strip can be processed quite smoothly during the rough rolling process, which helps to reduce surface defects in subsequent processing, and is also conducive to controlling the thickness tolerance and surface quality of the copper strip.
[0049] Further, in step S4, the heating treatment is performed in a bell-type furnace, and the parameters of the heating treatment are as follows: the temperature is 520-550°C, and the time is 4-6 hours. The present invention performs heating treatment in a bell-type furnace, and the temperature is set between 520-550°C, and the duration is 4-6 hours. The purpose is to eliminate work hardening, restore the ductility and processing properties of the material, and maintain it at a higher temperature for a certain time, which helps to promote recrystallization inside the material, eliminate internal stress, and improve the microstructure of the material, making it more suitable for subsequent fine processing.
[0050] Furthermore, in step S5, the intermediate rolling process is performed for a total of 5 passes. The present invention adopts the intermediate rolling process of the above passes, wherein each pass further thins the copper strip and optimizes its surface quality and mechanical properties, in preparation for subsequent fine processing.
[0051] Further, in step S5, a primary annealing treatment is performed in an air cushion furnace, and the parameters are as follows: temperature is 620-650°C, and time is 20-30s. In this technical solution, a primary annealing treatment is performed in an air cushion furnace, which can usually provide uniform temperature distribution and good atmosphere control, and is very suitable for rapid annealing treatment. At the same time, this technical solution sets the parameters of the above-mentioned primary annealing treatment. From the perspective of time, this technical solution adopts a rapid annealing treatment process. The main purpose of the rapid annealing treatment is to alleviate the work hardening of the material during the intermediate rolling process, restore its ductility and machinability, and maintain high production efficiency.
[0052] Furthermore, in step S5, the finishing rolling process is performed for a total of 5 passes, and the roughness of the roller is 0.15 μm. Similarly, the finishing rolling process is also performed for 5 passes, each of which further reduces the thickness of the copper strip, while ensuring the extremely high smoothness of the copper strip surface by using a roller with a roughness of 0.15 μm, which is crucial for the high-demand application of the final product.
[0053] Further, in step S5, the secondary annealing treatment is performed in a bell furnace, and the parameters are as follows: temperature is 280-320°C, and time is 3-5h. The present invention performs secondary annealing treatment in a bell furnace, which is usually used for annealing treatment of a longer period and can provide a more gentle and uniform heating environment. The above temperature and time are used to further eliminate residual stress, optimize the microstructure, and improve the conductivity of the material.
[0054] Further, in step S6, the finished product rolling is performed for a total of 4 passes, and the parameters are as follows: the roughness of the roller is 0.1 μm, the entrance tension is 300-400 KN, the rolling speed is 600-700 m / min, and the rolling force is 180-200 KN. The present invention adopts 4 passes of finished product rolling, each pass further thins the copper foil while maintaining or improving its surface flatness and mechanical properties. The four passes are usually set to gradually reach the final required ultra-thin thickness in the process of multiple slight thinnings while minimizing surface defects, and the 0.1 μm roller roughness indicates that the surface of the roller used for the finished product rolling is very smooth, which helps to produce ultra-thin copper foil with an extremely flat surface and reduce surface roughness; on this basis, the entrance tension is set within the range of 300-40 kN, which is to ensure that the copper foil maintains good straightness when entering the rolling mill, prevent the formation of wrinkles and edge waves, and also help to control the elongation of the material and ensure the consistency of thickness. The high-speed rolling of 600-700m / min means higher production efficiency, but the stability and surface quality of the material still need to be maintained at high speed, which requires high requirements for tension, thickness control and equipment stability. Combined with a rolling force of 180-200kN, it is sufficient to achieve the thinning goal while maintaining the integrity of the material, but without causing cracking or excessive work hardening.
[0055] The ultra-thin rolled copper foil obtained by the present technical solution has a thickness of 4-6μm, a pinhole rate of 3-7 pinholes / 10,000 meters, and a plate shape of 1-3I. The thickness of the ultra-thin rolled copper foil obtained by the present technical solution is precisely controlled between 4-6μm, which can provide better flexibility while maintaining sufficient conductivity and mechanical strength. The pinhole rate of the ultra-thin rolled copper foil obtained by the present invention is 3-7 pinholes / 10,000 meters, which indicates that the surface integrity of the copper foil is good, and the number of pinholes is controlled at a low level, which helps to improve the reliability and performance of the product. The plate shape is an indicator that describes the flatness and shape of the copper foil, which is represented by "I" (flatness index). The ultra-thin rolled copper foil obtained by the present invention has a plate shape of 1-3I, which means that the copper foil has good flatness and no waves or warping, which is very important for subsequent processing and use, such as occasions where precision fitting or welding is required during the manufacturing process.
[0056] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0057] Example 1
[0058] The present embodiment provides an ultra-thin rolled copper foil. The ultra-thin rolled copper foil is composed of the following components by mass percentage: Fe: ≤0.0004%, P: ≤0.0002%, O: 0.01%, and the balance is copper. The ultra-thin rolled copper foil of the present embodiment is prepared by the following preparation method:
[0059] S1. baking and heating high-purity electrolytic copper to obtain a molten casting material, wherein the copper content of the high-purity electrolytic copper is 99.99%, and the parameters of the baking and heating treatment are as follows: temperature is 150° C., and time is 10 min;
[0060] S2, putting the molten casting material obtained in step S1 into a smelting furnace for smelting, and after the smelting is completely static, oxygenation treatment is carried out by introducing compressed air to make the oxygen content evenly distributed in the copper liquid, and the molten copper is converted to a 1160° C. holding furnace and then covered with flake graphite, and then a rolled copper foil ingot is obtained by vertical full continuous casting, and the dew point value of the introduced compressed air is -60° C., and the moisture content is 0.02 g / m 3 ;
[0061] S3, subjecting the rolled copper foil ingot obtained in step S2 to heating treatment and hot rolling treatment in sequence to obtain a hot-rolled strip; wherein the heating treatment is carried out in a walking beam furnace, and the parameters of the heating treatment are as follows: the heating atmosphere is an oxidizing atmosphere, the temperature is 920° C., and the air-fuel ratio of the oxidizing atmosphere is 1.1; the parameters of the hot rolling treatment are as follows: a total of 7 passes, and the deformation amount of the 5th pass is 35%;
[0062] S4, subjecting the hot-rolled strip obtained in step S3 to milling treatment, rough rolling treatment and heating treatment in sequence to obtain a rough-rolled strip; wherein the parameters of the rough rolling treatment are as follows: a total of 7 passes, and the roughness of the roll in the rough rolling treatment is 0.5 μm; the heating treatment is carried out in a bell-type furnace, and the parameters of the heating treatment are as follows: the temperature is 520° C., and the time is 4 hours;
[0063] S5, the rough rolled strip obtained in step S4 is subjected to intermediate rolling treatment, primary annealing treatment, finishing rolling treatment and secondary annealing treatment in sequence to obtain a thick rolled copper foil; wherein the intermediate rolling treatment is carried out for a total of 5 passes; the primary annealing treatment is carried out in an air cushion furnace, and the parameters are as follows: the temperature is 620°C and the time is 20s; the finishing rolling treatment is carried out for a total of 5 passes, and the roughness of the rolling roll is 0.15μm; the secondary annealing treatment is carried out in a bell furnace, and the parameters are as follows: the temperature is 280°C and the time is 3h;
[0064] S6. The thick rolled copper foil obtained in step S5 is subjected to finished product rolling to obtain an ultra-thin rolled copper foil, wherein the finished product rolling is performed for a total of 4 passes, and the parameters are as follows: the roughness of the rolling roller is 0.1 μm, the inlet tension is 300 KN, the rolling speed is 600 m / min, and the rolling force is 180 KN.
[0065] Example 2
[0066] The present embodiment provides an ultra-thin rolled copper foil. The ultra-thin rolled copper foil is composed of the following components by mass percentage: Fe: 0.0002%, P: 0.0001%, O: 0.015%, and the balance is copper. The ultra-thin rolled copper foil of the present embodiment is prepared by the following preparation method:
[0067] S1. baking and heating high-purity electrolytic copper to obtain a molten casting material, wherein the copper content of the high-purity electrolytic copper is 99.99%, and the parameters of the baking and heating treatment are as follows: temperature is 170° C., and time is 11 minutes;
[0068] S2, putting the molten casting material obtained in step S1 into a smelting furnace for smelting, and after the smelting is completely static, oxygenation treatment is carried out by introducing compressed air to make the oxygen content evenly distributed in the copper liquid, and the converter is transferred to a 1160-1200° C. insulation furnace and then covered with flake graphite, and then a rolled copper foil ingot is obtained by vertical full continuous casting, and the dew point value of the introduced compressed air is -64° C., and the moisture content is 0.012 g / m 3 ;
[0069] S3, subjecting the rolled copper foil ingot obtained in step S2 to heating treatment and hot rolling treatment in sequence to obtain a hot-rolled strip; wherein the heating treatment is carried out in a walking beam furnace, and the parameters of the heating treatment are as follows: the heating atmosphere is an oxidizing atmosphere, the temperature is 930° C., and the air-fuel ratio of the oxidizing atmosphere is 1.12; the parameters of the hot rolling treatment are as follows: a total of 7 passes, and the deformation amount of the 5th pass is 36%;
[0070] S4, subjecting the hot-rolled strip obtained in step S3 to milling treatment, rough rolling treatment and heating treatment in sequence to obtain a rough-rolled strip; wherein the parameters of the rough rolling treatment are as follows: a total of 7 passes, and the roughness of the roll in the rough rolling treatment is 0.5 μm; the heating treatment is carried out in a bell-type furnace, and the parameters of the heating treatment are as follows: the temperature is 530° C., and the time is 4.5 h;
[0071] S5, the rough rolled strip obtained in step S4 is subjected to intermediate rolling treatment, primary annealing treatment, finishing rolling treatment and secondary annealing treatment in sequence to obtain a thick rolled copper foil; wherein the intermediate rolling treatment is carried out for a total of 5 passes; the primary annealing treatment is carried out in an air cushion furnace, and the parameters are as follows: the temperature is 630°C and the time is 22s; the finishing rolling treatment is carried out for a total of 5 passes, and the roughness of the rolling roll is 0.15μm; the secondary annealing treatment is carried out in a bell furnace, and the parameters are as follows: the temperature is 290°C and the time is 3.5h;
[0072] S6. The thick rolled copper foil obtained in step S5 is subjected to finished product rolling to obtain an ultra-thin rolled copper foil, wherein the finished product rolling is performed for a total of 4 passes, and the parameters are as follows: the roughness of the rolling roller is 0.1 μm, the inlet tension is 320 KN, the rolling speed is 6200 m / min, and the rolling force is 190 KN.
[0073] Example 3
[0074] The present embodiment provides an ultra-thin rolled copper foil. The ultra-thin rolled copper foil is composed of the following components by mass percentage: Fe: 0.0003%, P: 0.0002%, O: 0.02%, and the balance is copper. The ultra-thin rolled copper foil of the present embodiment is prepared by the following preparation method:
[0075] S1. baking and heating high-purity electrolytic copper to obtain a molten casting material, wherein the copper content of the high-purity electrolytic copper is 99.99%, and the parameters of the baking and heating treatment are as follows: temperature is 180° C., and time is 13 min;
[0076] S2, putting the molten casting material obtained in step S1 into a smelting furnace for smelting, and after the smelting is completely static, oxygenation treatment is carried out by introducing compressed air to make the oxygen content evenly distributed in the copper liquid, and the converter is transferred to a 1160-1200° C. insulation furnace and then covered with flake graphite, and then a rolled copper foil ingot is obtained by vertical full continuous casting, and the dew point value of the introduced compressed air is -70° C., and the moisture content is 0.005 g / m 3 ;
[0077] S3, subjecting the rolled copper foil ingot obtained in step S2 to heating treatment and hot rolling treatment in sequence to obtain a hot-rolled strip; wherein the heating treatment is carried out in a walking beam furnace, and the parameters of the heating treatment are as follows: the heating atmosphere is an oxidizing atmosphere, the temperature is 950° C., and the air-fuel ratio of the oxidizing atmosphere is 1.2; the parameters of the hot rolling treatment are as follows: a total of 7 passes, and the deformation amount of the 5th pass is 38%;
[0078] S4, subjecting the hot-rolled strip obtained in step S3 to milling treatment, rough rolling treatment and heating treatment in sequence to obtain a rough-rolled strip; wherein the parameters of the rough rolling treatment are as follows: a total of 7 passes, and the roughness of the roll in the rough rolling treatment is 0.5 μm; the heating treatment is carried out in a bell-type furnace, and the parameters of the heating treatment are as follows: the temperature is 550° C., and the time is 6 hours;
[0079] S5, the rough rolled strip obtained in step S4 is subjected to intermediate rolling treatment, primary annealing treatment, finishing rolling treatment and secondary annealing treatment in sequence to obtain a thick rolled copper foil; wherein the intermediate rolling treatment is carried out for a total of 5 passes; the primary annealing treatment is carried out in an air cushion furnace, and the parameters are as follows: the temperature is 650° C., and the time is 30 s; the finishing rolling treatment is carried out for a total of 5 passes, and the roughness of the rolling roll is 0.15 μm; the secondary annealing treatment is carried out in a bell furnace, and the parameters are as follows: the temperature is 320° C., and the time is 5 h;
[0080] S6. The thick rolled copper foil obtained in step S5 is subjected to finished product rolling to obtain an ultra-thin rolled copper foil, wherein the finished product rolling is performed for a total of 4 passes, and the parameters are as follows: the roughness of the rolling roller is 0.1 μm, the inlet tension is 350 KN, the rolling speed is 700 m / min, and the rolling force is 200 KN.
[0081] Example 4
[0082] The present embodiment provides an ultra-thin rolled copper foil. The ultra-thin rolled copper foil is composed of the following components by mass percentage: Fe: 0.0002%, P: 0.0001%, O: 0.024%, and the balance is copper. The ultra-thin rolled copper foil of the present embodiment is prepared by the following preparation method:
[0083] S1. baking and heating high-purity electrolytic copper to obtain a molten casting material, wherein the copper content of the high-purity electrolytic copper is 99.99%, and the parameters of the baking and heating treatment are as follows: temperature is 220° C., and time is 15 min;
[0084] S2, putting the molten casting material obtained in step S1 into a smelting furnace for smelting, and after the smelting is completely static, oxygenation treatment is carried out by introducing compressed air to make the oxygen content evenly distributed in the copper liquid, and the molten copper is converted to a 1200° C. holding furnace and then covered with flake graphite, and then a rolled copper foil ingot is obtained by vertical full continuous casting, and the dew point value of the introduced compressed air is -68° C., and the moisture content is 0.008 g / m 3 ;
[0085] S3, subjecting the rolled copper foil ingot obtained in step S2 to heating treatment and hot rolling treatment in sequence to obtain a hot-rolled strip; wherein the heating treatment is carried out in a walking beam furnace, and the parameters of the heating treatment are as follows: the heating atmosphere is an oxidizing atmosphere, the temperature is 950° C., and the air-fuel ratio of the oxidizing atmosphere is 1.2; the parameters of the hot rolling treatment are as follows: a total of 7 passes, and the deformation amount of the 5th pass is 38%;
[0086] S4, subjecting the hot-rolled strip obtained in step S3 to milling treatment, rough rolling treatment and heating treatment in sequence to obtain a rough-rolled strip; wherein the parameters of the rough rolling treatment are as follows: a total of 7 passes, and the roughness of the roll in the rough rolling treatment is 0.5 μm; the heating treatment is carried out in a bell-type furnace, and the parameters of the heating treatment are as follows: the temperature is 550° C., and the time is 6 hours;
[0087] S5, the rough rolled strip obtained in step S4 is subjected to intermediate rolling treatment, primary annealing treatment, finishing rolling treatment and secondary annealing treatment in sequence to obtain a thick rolled copper foil; wherein the intermediate rolling treatment is carried out for a total of 5 passes; the primary annealing treatment is carried out in an air cushion furnace, and the parameters are as follows: the temperature is 650° C., and the time is 30 s; the finishing rolling treatment is carried out for a total of 5 passes, and the roughness of the rolling roll is 0.15 μm, and the secondary annealing treatment is carried out in a bell furnace, and the parameters are as follows: the temperature is 320° C., and the time is 5 h;
[0088] S6. The thick rolled copper foil obtained in step S5 is subjected to finished product rolling to obtain an ultra-thin rolled copper foil, wherein the finished product rolling is performed for a total of 4 passes, and the parameters are as follows: the roughness of the rolling roller is 0.1 μm, the inlet tension is 400 KN, the rolling speed is 700 m / min, and the rolling force is 200 KN.
[0089] Comparative Example 1
[0090] This comparative example provides an ultra-thin rolled copper foil, which is different from Example 3 only in that the content of Fe element in this comparative example is 0.0007%, and the rest is the same as Example 3, which will not be repeated here.
[0091] Comparative Example 2
[0092] This comparative example provides an ultra-thin rolled copper foil, which is different from Example 3 only in that the content of P element in this comparative example is 0.0005%, and the rest is the same as Example 3, which will not be described again.
[0093] Comparative Example 3
[0094] This comparative example provides an ultra-thin rolled copper foil, which is different from Example 3 only in that the content of O element in this comparative example is 0.008%, and the rest is the same as Example 3, which will not be described again.
[0095] Comparative Example 4
[0096] This comparative example provides an ultra-thin rolled copper foil, which is different from Example 3 only in that the content of O element in this comparative example is 0.026%, and the rest is the same as Example 3, which will not be repeated here.
[0097] Comparative Example 5
[0098] This comparative example provides an ultra-thin rolled copper foil, which is different from Example 3 only in that the preparation method of this comparative example does not include step S1, and the rest is the same as Example 3, which will not be repeated here.
[0099] Comparative Example 6
[0100] This comparative example provides an ultra-thin rolled copper foil, which differs from Example 3 only in that, during the preparation process of this comparative example, no flake graphite covering is used in step S2, and the rest is the same as Example 3 and will not be repeated here.
[0101] Comparative Example 7
[0102] This comparative example provides an ultra-thin rolled copper foil, which is different from Example 3 only in that, during the preparation process of this comparative example, in step S3, the deformation amount of the 5th pass is 33%, and the rest is the same as Example 3, which will not be repeated here.
[0103] Comparative Example 8
[0104] This comparative example provides an ultra-thin rolled copper foil, which is different from Example 3 only in that, during the preparation process of this comparative example, in step S3, the deformation amount of the fifth pass is 40%, and the rest is the same as Example 3, which will not be repeated here.
[0105] Comparative Example 9
[0106] This comparative example provides an ultra-thin rolled copper foil, which is different from Example 3 only in that, during the preparation process of this comparative example, in step S4, the roughness of the rolling roller is 0.7 μm, and the rest is the same as Example 3, which will not be repeated here.
[0107] Comparative Example 10
[0108] This comparative example provides an ultra-thin rolled copper foil, which is different from Example 3 only in that, during the preparation process of this comparative example, in step S5, the roughness of the roller in the finish rolling process is 0.2 μm, and the rest is the same as Example 3 and will not be repeated here.
[0109] The ultra-thin rolled copper foils obtained in Examples 1-4 and Comparative Examples 1-10 were subjected to performance tests, and the test results are shown in Table 1:
[0110] Table 1: Performance test results of ultra-thin rolled copper foils obtained in Examples 1-4 and Comparative Examples 1-10
[0111] Logo Copper foil thickness / μm Pinhole rate / 10,000 meters Plate shape / I Copper foil roughness / μm Example 1 4 5 1 0.05 Example 2 5 4 3 0.06 Example 3 6 7 2 0.08 Example 4 5 3 1 0.07 Comparative Example 1 8 40 6 0.10 Comparative Example 2 10 50 8 0.12 Comparative Example 3 8 42 7 0.13 Comparative Example 4 10 45 8 0.11 Comparative Example 5 9 35 6 0.11 Comparative Example 6 9 34 7 0.12 Comparative Example 7 8 44 5 0.11 Comparative Example 8 6 45 6 0.13 Comparative Example 9 5 37 6 0.12 Comparative Example 10 6 36 7 0.14
[0112] It can be seen from the above data results that the technical solution reduces the probability of pinhole defects at each stage by selecting and processing raw materials and combining the key process parameters in the preparation steps, improves the plate shape of the foil, and ensures that the ultra-thin rolled copper foil can achieve the purpose of low pinhole rate and excellent plate shape under the premise of meeting the thickness requirements; specifically, referring to the results of Example 3 and Comparative Examples 1 and 2, it can be seen that when Fe and P as impurity elements in the copper foil are excessive, it will have a certain negative impact on the quality of the obtained copper foil. The reasons are as follows: Iron particles act as heterogeneous nucleation sites, promote the formation of defects in the copper crystallization process, and lead to the generation of pinholes. Copper and iron can form intermetallic compounds under certain conditions. The physical properties of these compounds (such as hardness and brittleness) are different from those of copper, which may cause changes in the microstructure of the copper foil and increase the possibility of pinholes. Another possible reason is that the thermal expansion coefficients of iron and copper are different. When the copper foil undergoes temperature changes, different stresses may be generated between iron and copper, resulting in cracks inside the material. These cracks may further develop to form pinholes. During the heat treatment of copper foil, a small amount of phosphorus can inhibit the recrystallization of copper foil and refine the grains, but excessive phosphorus may cause grain boundary segregation and form a brittle phase, thereby generating microcracks during heat treatment or subsequent processing. These microcracks may develop into pinholes to a certain extent. The solid solution strengthening effect of phosphorus in copper can improve the hardness and strength of copper, but excessive phosphorus will form brittle Cu-P compounds. These compounds are unevenly distributed in the copper matrix, which may cause local stress concentration and increase the risk of pinhole formation. In summary, as impurity elements, Fe and P elements need to strictly control their content within the range described in this technical solution.
[0113] Specifically, by comparing Example 3 with Comparative Examples 3 and 4, it can be found that no matter the content of oxygen is lower or higher than the content of O element specified in the technical solution, it will have a negative impact on the quality of the finally obtained rolled copper foil. Considering that at a low oxygen content, oxygen can act as a nucleating agent in the recrystallization process, which helps to control the grain size, thereby indirectly reducing the formation of pinholes. At the same time, an appropriate amount of oxygen can inhibit the grain growth of the copper foil during the heat treatment process, thereby maintaining a relatively uniform microstructure, which theoretically helps to reduce the formation of pinholes caused by discontinuous grain boundaries; however, excessive oxygen in the copper foil can form oxides with copper, such as Cu2O, and these oxides may form discontinuous phases in the copper foil, resulting in local stress concentration and increasing the risk of pinhole formation. Moreover, during high-temperature heat treatment, oxygen can accelerate the oxidation of copper to form oxide scales. The uneven distribution or desorption of these oxides may cause pores inside the copper foil, i.e., pinholes. Therefore, in actual production, it is necessary to control the content of oxygen within the scope disclosed in the technical solution.
[0114] Further, referring to Comparative Example 5 and Example 3, it can be further seen that the baking heating pretreatment has an effect on the technical solution. Considering that the water and oil on the surface are not completely removed, the ingot has internal defects in the subsequent preparation process. It can be seen that in the copper foil preparation process, the pretreatment also has an important effect on the performance. Referring to Comparative Example 6 and Example 3, it can be seen that the copper foil obtained after the flake graphite coating has better performance. Considering the effect of the flake graphite coating on the performance of the copper foil is mainly reflected in: the flake graphite can provide a good covering effect, reduce the air intake of the holding furnace, and thus obtain a rolled copper foil ingot with better internal quality.
[0115] It can be seen from the results of Comparative Examples 7-10 and Example 3 that both the deformation and the roughness of the rollers during the rolling process have a certain influence on the pinhole rate and roughness of the copper foil finally obtained. The reasons are as follows: First, if the deformation is too large, a higher stress will be generated in the copper foil material, which may cause cracks or delamination inside the material, thereby increasing the formation of pinholes. Excessive deformation may also cause defects in the material to expand, such as inclusions or microcracks at grain boundaries, which may evolve into pinholes; if the deformation is too low, the shape is difficult to control, and the surface roughness of the copper foil cannot reach the range required by the present invention; second, if the deformation is too large, the copper foil material will be more prone to cracks or delamination, which may cause the formation of pinholes. The size of the deformation will affect the crushing and rearrangement of the grains. A reasonable deformation amount helps to refine the grains, thereby improving the surface roughness of the copper foil. If the deformation amount is too large, the grains may be over-crushed, resulting in increased surface irregularities and increased roughness. Third, excessive roughness of the roll may introduce additional tiny cracks or defects on the surface of the copper foil, which may develop into pinholes during subsequent processing. In addition, if there are hard spots or foreign matter on the surface of the roll, scratches will be caused on the surface of the copper foil, and these scratches may also be converted into pinholes during subsequent heat treatment or processing. Fourth, the roughness of the roll directly determines the surface state of the copper foil. If the surface of the roll is too rough, the surface of the copper foil will also inherit this roughness, resulting in an uneven surface of the final product. Conversely, if the surface of the roll is too smooth, it may not be conducive to the bite of the material, but may lead to poor surface finish.
[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An ultra-thin rolled copper foil, characterized in that: The ultra-thin rolled copper foil is composed of the following components in percentage by mass: composition: Fe: ≤0.0005%, P: ≤0.0003%, O: 0.01-0.024%, and the balance is copper.
2. A method for preparing an ultra-thin rolled copper foil as claimed in claim 1, characterized in that: The preparation method specifically comprises the following steps: S1, baking and heating high-purity electrolytic copper to obtain a molten casting material; S2, putting the molten casting material obtained in step S1 into a smelting furnace for smelting, and after the smelting is completely static, performing an oxygenation treatment to make the oxygen content evenly distributed in the copper liquid, and covering it with flake graphite after transferring it from the converter to the holding furnace, and then obtaining a rolled copper foil ingot by vertical full continuous casting; S3, subjecting the rolled copper foil ingot obtained in step S2 to heating treatment and hot rolling treatment in sequence to obtain a hot-rolled strip; S4, subjecting the hot-rolled strip obtained in step S3 to milling treatment, rough rolling treatment and heating treatment in sequence to obtain a rough-rolled strip; S5, subjecting the rough-rolled strip obtained in step S4 to intermediate rolling, primary annealing, finish rolling and secondary annealing in sequence to obtain a thick rolled copper foil; S6, rolling the thick rolled copper foil obtained in step S5 into a finished product to obtain an ultra-thin rolled copper foil.
3. The method for preparing the ultra-thin rolled copper foil according to claim 2, characterized in that: In the step S1, the copper content of the high-purity electrolytic copper is ≥99.99%, and the parameters of the baking and heating treatment are as follows: the temperature is 150-220° C., and the time is 10-15 min.
4. The method for preparing the ultra-thin rolled copper foil according to claim 2, characterized in that: In step S2, the oxygenation treatment is carried out by introducing compressed air, and the dew point of the introduced compressed air is -60 to -70°C, and the moisture content is 0.005 to 0.02 g / m 3 ; and / or, the temperature of the holding furnace is 1160-1200°C.
5. The method for preparing the ultra-thin rolled copper foil according to claim 2, characterized in that: In the step S3, the heating treatment is carried out in a walking furnace, and the parameters of the heating treatment are as follows: the heating atmosphere is an oxidizing atmosphere, the temperature is 920-950°C, and the air-fuel ratio of the oxidizing atmosphere is 1.1-1.2; and / or, in the step S3, the parameters of the hot rolling treatment are as follows: a total of 7 passes, and the deformation of the 5th pass is 35-38%.
6. The method for preparing the ultra-thin rolled copper foil according to claim 2, characterized in that: In the step S4, the parameters of the rough rolling treatment are as follows: a total of 7 passes, and the roughness of the roller in the rough rolling treatment is 0.5 μm; and / or, in the step S4, the heating treatment is carried out in a bell-type furnace, and the parameters of the heating treatment are as follows: the temperature is 520-550° C., and the time is 4-6 hours.
7. The method for preparing the ultra-thin rolled copper foil according to claim 2, characterized in that: In the step S5, the intermediate rolling process is performed for a total of 5 times; and / or, in the step S5, an annealing process is performed in an air cushion furnace with the following parameters: temperature of 620-650° C. and time of 20-30 seconds.
8. The method for preparing the ultra-thin rolled copper foil according to claim 2, characterized in that: In the step S5, the finishing rolling process is performed for 5 passes in total, and the roughness of the rolling roller is 0.15 μm; and / or, in the step S5, the secondary annealing process is performed in a bell furnace, and the parameters are as follows: temperature is 280-320° C., and time is 3-5 hours.
9. The method for preparing the ultra-thin rolled copper foil according to claim 2, characterized in that: In step S6, the finished product is rolled for 4 times in total, and the parameters are as follows: the roughness of the roller is 0.1 μm, the inlet tension is 300-400 KN, the rolling speed is 600-700 m / min, and the rolling force is 180-200 KN.
10. The method for preparing the ultra-thin rolled copper foil according to claim 2, characterized in that: The thickness of the ultra-thin rolled copper foil is 4-6μm, the pinhole rate is 3-7 pinholes / 10,000 meters, and the plate shape is 1-3I.
